Why do central states accept holding independence referendums? Analyzing the role of state peripheries. (February 2021) - Harguindéguy, Jean-Baptiste; Sánchez, Enrique Sánchez; Sánchez, Almudena Sánchez
Abstract: Why do central states accept holding independence referendums if they could lose a part of their territory during this process? Several variables have been proposed to explain this contradiction, but the most robust one has proved to be the competition-proximity model formulated by Qvortrup (2014). This paper challenges this theory by stressing the role of state peripheries. According to our approach, central governments are more likely to risk losing poor and isolated territories if they represent a cost for the host state. Drawing on an updated version of the contested sovereignty data set (1776–2019) by Mendez and Germann (2018), this paper demonstrates statistically that the "peripheriness" variables related to the economy and – especially – location are significant. Consequently, the competition-proximity model remains the best-fitted scheme for explaining central governments' decision-making, but it can be amended slightly by taking into account the peripheral nature of separatist regions.